Philosophical Meaning of Jathilan Dance Movements in Reog Obyog Traditional Art - Putri Dyah Indriyani; Agus Cahyono; Tutung Nurdiyana; Eko Sugiarto (International Conference on Science, Education, and Technology, 2023)
Jathilan dance is one of the traditional dances that are part of the Reog Obyog art from East Java, Indonesia. This dance is characterized by the use of horses' masks and the movements that imitate the movement of horses. The purpose of this study is to identify and explain the philosophical meaning of the Jathilan dance in the Reog Obyog art. The research method used is a qualitative approach with observation, interviews, and document analysis as data collection techniques. Data analysis is carried out using content analysis. The results show that the Jathilan dance has philosophical meanings that are closely related to the Javanese culture. The dance movements depict the values of bravery, power, and wisdom, which are important values in the Javanese culture. The Jathilan dance in the Reog Obyog art is a representation of the cultural identity of the Javanese people. The dance movements symbolize the connection between the human and the natural world, where the human being is seen as an integral part of nature. The horse mask represents the spirit of the horse, which is an important animal in the Javanese culture. The sound of the gamelan, which accompanies the dance, represents the harmony between human beings and nature. In conclusion, the Jathilan dance in the Reog Obyog art has significant philosophical meanings that reflect the Javanese culture. This dance is a form of cultural expression that portrays the values and beliefs of the Javanese people. This study contributes to the understanding of the Javanese culture and the significance of traditional art forms in preserving cultural heritage.